1998
DOI: 10.2307/3434318
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogenicity of Bisphenol A-Related Diphenylalkanes with Various Substituents at the Central Carbon and the Hydroxy Groups

Abstract: The chemical structure of hydroxylated diphenylalkanes or bisphenols consists of two phenolic rings joined together through a bridging carbon. This class of endocrine disruptors that mimic estrogens is widely used in industay, particularly in plastics. Bisphenol F, bisphenol A, fluorinecontaining bisphenol A (bisphenol AF), and other diphenylalkanes were found to be estrogenic in a bioassay with MCF7 human breast cancer cells in culture (ESCREEN assay). Bisphenols promoted cell proliferation and increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 23 publications
2
56
0
1
Order By: Relevance
“…This BPA concentration is compatible with the maximum estrogenic activity observed in MCF-7 cells (43,44).…”
Section: Discussionsupporting
confidence: 82%
“…This BPA concentration is compatible with the maximum estrogenic activity observed in MCF-7 cells (43,44).…”
Section: Discussionsupporting
confidence: 82%
“…The longer the side chain, the greater the binding affinity for the ER (35). Common pharmacophore identification indicated that the optimal structural superposition between bisphenol A and E 2 is one in which the two benzene rings of bisphenol A are positioned over the A and C rings of E 2 , with the bridge carbon overlaying the B ring ( Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…7 Particular public interests have also been focused on the potential health impact and exposure risk assessments on these estrogenic xenobiotics. 8 However, despite their extensive usage in industry and commercial applications, there is still a lack of knowledge about the release patterns and environmental occurrence of some of the BPs, which is essential to better estimate potential exposure routes to human. Current monitoring studies mostly focus on a small fraction of BP analogues, mainly on BPA which is the dominant BP and is utilized as a monomer in the production of polycarbonate plastics and epoxy resins.…”
Section: ■ Introductionmentioning
confidence: 99%